Drawing Skill is Related to the Efficiency of Encoding Object Structure. (April 2014) - Perdreau, Florian; Cavanagh, Patrick
Accurate drawing calls on many skills beyond simple motor coordination. A good internal representation of the target object's structure is necessary to capture its proportion and shape in the drawing. Here, we assess two aspects of the perception of object structure and relate them to participants' drawing accuracy. First, we assessed drawing accuracy by computing the geometrical dissimilarity of their drawing to the target object. We then used two tasks to evaluate the efficiency of encoding object structure. First, to examine the rate of temporal encoding, we varied presentation duration of a possible versus impossible test object in the fovea using two different test sizes (8° and 28°). More skilled participants were faster at encoding an object's structure, but this difference was not affected by image size. A control experiment showed that participants skilled in drawing did not have a general advantage that might have explained their faster processing for object structure. Second, to measure the critical image size for accurate classification in the periphery, we varied image size with possible versus impossible object tests centered at two different eccentricities (3° and 8°). More skilled participants were able to categorise object structure at smaller sizes, and this advantage did not change with eccentricity. A control experiment showed that the result could not be attributed to differences in visual acuity, leaving attentional resolution as a possible explanation. Overall, we conclude that drawing accuracy is related to faster encoding of object structure and better access to crowded details.